Wireless Photoplethysmography (PPG) Measurement with Pulse Wave Velocity (PWV) Method for Arterial Stiffness Evaluation - Dewi, Ervin Masita; Rahmawati, Dini; Kirana, Nurista Wahyu (Universitas Syiah Kuala, 2024)
Indications of symptoms of cardiovascular disease can be seen from the level of elasticity of the arteries. The Pulse Wave Velocity (PWV) method using PPG signal analysis is used to determine the level of arterial stiffness based on the time difference between pulse waves of Photoplethysmography (PPG) signal measurements. PWV measurements use a non-invasive technique using pulse sensors on the fingers and toes, the measurement data is sent wirelessly using the ESP-NOW protocol. Analysis of the measured PPG signal is used as an approach to calculating the PWV value. Realization and testing can be used to measure the pulse in BPM and classify the index of arterial stiffness using the PWV method. The results of testing on 15 test volunteers from 3 age groups showed the results of an arterial stiffness index with indications of normal, stiff and very stiff arteries. The PWV value for the 20 year old group was 4.30-6.77 cm/s, normal arterial conditions. The age group of 30-40 years has a PWV value ranging from 5.11-8.77 cm/s, normal arterial conditions. The age group of 50-60 years had PWV values in the range of 10.69-18.43 cm/s, stiff and very stiff arterial conditions. Increasing age linearly affects the increase in PWV value. An increased PWV value may indicate an increase in arterial stiffness.